MUNDARDJITO, CAGAR BUDAYA DAN IDENTITAS BANGSA (KRITIS, 2022)
This paper presents Mundardjito's role as an academic-cum-intellectual in the field of Archeology. His role in the development of the discipline of Archeology can be traced from his dissertation related to space-archeology which is influential in environmental archeology, especially on the relationship between cultural heritage, environment and culture. He developed the thesis in an academic discourse that operates in academia, bureaucrats and the community. His intellectual outlook is very clear where he stands tall among the porous buildings of the Indonesian nation's character. His views on development with the perspective of preserving cultural heritage are parallel to those of several academics, including Cagmani who put forward an endogenous approach and Tanudirjo who saw cultural heritage as inseparable from the dynamics of contemporary culture and its social landscape.